Culturally Responsive Teaching: Navigating Models and Implementing Effective Strategies - Abdalla, Hassan; Moussa, Ahmat (Tecno Scientifica Publisher, 2024)
Culturally Responsive Teaching (CRT) stands as a beacon of equity and inclusivity within the realm of education, advocating for instructional practices that honor and affirm students' diverse cultural backgrounds, experiences, and perspectives. It bridges the cultural divide between educators and students, recognizing that cultural identities significantly shape learning experiences and outcomes. The aim of this review is to thoroughly analyze CRT, delving into its diverse models, strategies, and practical implications. CRT emphasizes cultural competence among educators, the integration of culturally relevant content into the curriculum, and fostering positive teacher-student relationships. Models developed by scholars such as James A. Banks, Geneva Gay, and Gloria Ladson-Billings provide practical frameworks for CRT implementation, promoting culturally inclusive teaching methods and nurturing positive intercultural interactions. Implementing CRT involves creating inclusive curriculum, cultivating cultural competence among educators, and fostering positive teacher-student relationships. However, challenges such as implicit bias, structural barriers, and language diversity must be addressed to create supportive learning environments. Moving forward, enhancing teacher education programs, providing ongoing professional development, and advocating for policies that support equity and inclusion are essential steps to advance culturally responsive practices in education. Collaborative efforts among educators, researchers, policymakers, and community stakeholders are vital for promoting equity, fostering collaboration, and improving outcomes for all students in culturally diverse educational settings.